THE INFLUENCE OF QUEUEING SYSTEM AND SUPERVISION ON SERVICE QUALITY IN JAKARTA MRT TRANSPORTATION - Daman Sudarman (Transpublika Publisher, 2023)
This study aims to analyze the impact of the queuing system and supervision on service quality in Jakarta MRT transportation. This research is quantitative research. Data for this research was gathered from interviews, direct requests from relevant companies, and secondary sources like government publications, company records, media analysis, and websites. The study's population included MRT Jakarta transportation users over a one-week period, and the sample consisted of 50 customers selected using Systematic Random Sampling. Data was collected through questionnaires and interviews and analyzed using statistical analysis with SPSS application. The results of this study are as follows: there is an influence between the queuing system and service quality, there is an influence between supervision and service quality partially, and there is an effect between the queuing system and supervision on the quality of service simultaneously 78.2%, while the remaining 21.8% is influenced by other variables.